Influence of plant growth-promoting rhizobacteria inoculation on nutrient availability, soil microbial properties and defence enzymes in rice (Oryza sativa) crop - MEENA, R K; SINGH, Y V; LATA, LATA; PRASANNA, R; KAUR, C; KUMAR, A; BANA, R S (The Indian Journal of Agricultural Sciences, 2014)
Soil organic carbon, available N, P, K, Zn, Fe and Cu in soil at crop harvest stage significantly increased due to the integrated inoculation of PGPR and Multani mitti based BGA with application of compost and chemical N fertilizer (80 and 120 kg/ha) over N control. Status of SOC and available N, P, K, Fe, Zn and Cu in soil at crop maturity stage was highest at 2/3N+BI+CI+C@ 5.0 tonnes/ha. Soil chlorophyll, dehydrogenase and ARA activity were significantly higher at 2/3N+BI+CI+C@ 5.0 tonnes/ha compared to other treatments. Plant enzymatic activity of POD and PPO at 60 DAT also was significantly higher in 2/3N+BI+CI+Compost@ 5.0 tonnes/ha. Application of 2/ 3N with inoculation of bacterial and cyanobacterial PGPR along with 5.0 tonnes/ha compost not only improved nutrient availability in soil but also enhanced soil microbial, plant enzymatic activity and crop yield.